Sosialisasi Digital Marketing Pada UMKM Kerupuk Kulit Di Desa Kediri Induk Kecamatan Kediri Kabupaten Lombok Barat - Baiq Kisnawati; Ni Nyoman Yuliati; I Made Suardana; Topan Siswanto; Hikmah; Sukma Hidayat Kurnia Abadi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
Kediri Induk is a village located in Kediri sub-district, West Lombok district. This village is a village that has many Micro, Small and Medium Enterprises (MSMEs). One of the MSMEs in Kediri Induk village is the very promising Murni Leather Crackers MSME, namely processing cowhide into cowhide cracker products. The problems currently faced by MSMEs are weak product innovation and weak marketing networks. To motivate and develop these MSMEs by providing an innovation that is more attractive than previous products both in terms of packaging, flavor variants, logos and marketing networks. After motivation and assistance, this MSME succeeded in developing its production with new variants and succeeded in marketing its products through digital marketing